Dialogic literary gatherings: tool for success in education (Journal of Parents and Teachers, 2016)
Dialogic literary gatherings (DLG) were something completely different at this school in Cambridgeshire. Through dialogic interactions between students and teachers, they improved both their academic performance and their relationships, sharing words and deep feelings.
Keywords: Dialogic literary gatherings; dialogic interactions; academic achievement; values development.